Epidemiology of snakebites recorded in epidemiological surveillance in the municipality of Rio Verde - Goiás, Brazil - Menezes Filho, Antonio Carlos Pereira de; Cabral, Silvia Rosana Pagliarini (Brazilian Journal of Science, 2022)
The present study aimed to evaluate the cases of snakebites registered in the municipality of Rio Verde-GO, Brazil, between january 2007 and november 2010. Data collected by the Notifiable Diseases Information System - Ministry of Health at epidemiological surveillance of the municipality. The results obtained were organized based on the number of accidents, gender of the snake, circumstance of the accident, monthly and annual distribution, seasonality distribution, age group and sex of the individuals, affected anatomical region, time elapsed from the accident/care, evolution or clinical picture and classification by severity. Ophidian accidents were caused by the genera Bothrops, Crotalus, Micrurus and ignored cases, totaling 89 accidents. The highest rate of accidents was with the genus Bothrops (17) and 20 ignored cases, where it was not possible to identify the species. There was a predominance of accidents in the months between december to march (hot and rainy season) with 46 cases (64.05%). Most accidents occurred in the countryside with 75 cases. Records predominated in males (68 cases) and aged 11-29 years. The anatomical region most affected were legs and feet. The time elapsed between the accident and the service prevailed between 1 and 2 hours, where 86.51% of the cases evolved to cure. There were no death records, and 20.22% of the cases were classified as mild and 58.42% as moderate. In conclusion, the results obtained in this study are in line with other studies presented. Ophidian accidents are still a public health problem in Brazil, and data are still scarce in order to understand the severity and establish protocols with greater agility and in a shorter time between ophidism and healing.